Tegaserod Maleate Inhibits Esophageal Squamous Cell Carcinoma Proliferation by Suppressing the Peroxisome Pathway - Wu, Xiangyu; Wang, Zitong; Jiang, Yanan; Zhou, Hao; Li, Ang; Wei, Yaxing; Bao, Zhuo; Wang, Donghao; Zhao, Jimin; Chen, Xinhuan; Guo, Yaping; Dong, Zigang; et al. (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are the two major types of esophageal cancer (EC). ESCC accounts for 90% of EC, and recurrence after primary treatment is common. Preventing recurrence is a promising strategy for extending the 5-year survival rate in patients. We found that tegaserod maleate could inhibit ESCC proliferation both in vivo and in vitro. Through proteomics analysis, we found that tegaserod maleate suppressed the peroxisome signaling pathway, in which the key molecules peroxisome membrane protein 11B (PEX11B) and peroxisome membrane protein 13 (PEX13) were downregulated. The immunofluorescence results, catalase activity assay, and detection of reactive oxygen species (ROS) confirmed that downregulation of these proteins was related to impaired peroxisome function. We found that tegaserod maleate was highly expressed in ESCC, and knockout of PEX11B and PEX13 further demonstrated the antitumor effect of tegaserod maleate. Importantly, tegaserod maleate repressed ESCC tumor growth in a patient-derived xenograft (PDX) model in vivo. Our findings conclusively demonstrated that tegaserod maleate inhibits the proliferation of ESCC by suppressing the peroxisome pathway. Further, the new use of old drugs in the treatment of ESCC is highlighted and we show that tegaserod maleate may be an effective treatment for EC.